First record of the genus Goreopagurus McLaughlin, 1988 (Crustacea: Anomura: Paguroidea) from Brazil, with description of a new species - Nucci, Paulo R.; de Melo, Gustavo A.s. (Zootaxa, 2007)
The genus Goreopagurus McLaughlin, 1988 was erected for Pagurus piercei Wass, the description of which was based on a single male. Prior to the present study Goreopagurus was represented by three species: G. piercei (Wass, 1963); G. garthi McLaughlin & Haig, 1995; and G. poorei Lemaitre & McLaughlin, 2003. Herein we record the first occurrence of the genus Goreopagurus from Brazil, and add the fourth species to the genus.